Pengembangan Keterampilan Guru Dalam Inovasi Pembelajaran Berbasis TPACK (Technological Pedagogical Content Knowledge) Bagi Guru SMP Maria Goretti Semarang - Susanti, Martien; Prihanto, At. Sugeng; Sunarto, Sunarto (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Innovative learning combines information and communication technology as well as collaboration between students and teachers based on higher-order thinking skills (HOTS) with a focus on 21st-century learning skills. This learning is packaged in the TPACK (Technological, Pedagogical, and Content Knowledge) platform. The problem faced by partners is that teachers are not yet fully able to implement TPACK-based innovative learning. This community service aims to provide training and assistance so that teachers can implement innovative TPACK-based learning. The service methods used are training and mentoring. Service activities consist of three stages: preparation, implementation, and evaluation. The final results of the training and mentoring carried out were the level of mastery of knowledge and information in the field of technology-based learning media (such as Canva, Virtual Reality, and Augmented Reality) reaching 85%, mastery of innovative learning models (Problem-Based Learning and Project Based Learning at 90%, and the ability to compose TPACK-based teaching modules was 87%. Thus it can be concluded that the training and mentoring carried out has proven successful in developing teachers' skills in implementing TPACK-based innovative learning.